Tipo de pasteurización y temperatura de almacenamiento en la estabilidad fisicoquímica, microbiológica y sensorial del néctar mix de cítricos con sábila - Vera Bravo, Adriana Fernanda (2021)
The present investigation was carried out with the objective of determining the type of pasteurization and the storage temperature that guarantee the physicochemical, microbiological and sensory stability of the nectar mix of orange (Citrus sinnensis), mandarin (Citrus reticulata), lemon (Citrus lemon L.) and aloe (Aloe vera), prolonging its shelf life. Two types of pasteurization were considered (Factor A) Slow (75°C / 10 min) and Fast (85°C / 3 min) and three storage temperatures (Factor B) 4, 20 and 27°C, obtaining 6 treatments. A Bifactorial A*B design conducted in a Completely Random Block Design with three repetitions and the Labuza equation was applied to determine the best treatment in useful life time; Six 330 mL glass containers of citrus nectar mix with aloe were used as an experimental unit. Measurements of physicochemical parameters (pH, acidity, °Brix, density, viscosity and sedimentation rate), microbiological (Coliforms, Fecal Coliforms, Mesophilic aerobes, molds and yeasts) and sensory attributes (color, odor, taste and consistency) were carried out at the finished product. The data of these physicochemical parameters and sensory attributes were processed using the SPSS Statistic program free version. It was concluded that the most suitable type of pasteurization that preserves the physicochemical, microbiological and sensory attributes of the citrus nectar mix with aloe is slow pasteurization (75°C / 10 min) and the storage temperature that guarantees its stability is of 4°C. The shelf life of the nectar mix at a microbiological level is 7 days and at a physical-chemical level it is 9 days.